Implementasi Metode Bermain Peran Pada Pembelajaran IPS di MI Muhammadiyah Bandingan Kecamatan Kejobong Kabupaten Purbalingga - Ariyanto Ariyanto; Nurfuadi Nurfuadi (Journal on Education, 2023)
This research is a field research (field research). While the research method uses a descriptive qualitative approach with data collection techniques using observation, interviews and documentation. The data validity technique uses triangulation. This study describes: (1) planning a role-playing method in social studies learning; (2) implementation of role playing method in social studies learning; (3) evaluation of role playing methods in social studies learning; (4) the strengths and weaknesses of the role-playing method; and (5) analysis of the application of role-playing methods in social studies learning at MI Muhammadiyah Bandingan, Kejobong District, Purbalingga Regency. The results showed: (1) Before implementing the role-playing method in social studies learning, the classroom teacher prepared lesson plans, media/equipment to be used, evaluation and appropriate strategies, and prepared story scenarios. (2) The initial activity in the implementation of the role playing method is carried out by providing motivation and conveying the material to be discussed and the learning method to be used. Entering the core activity, the teacher begins to implement the previously prepared method. The final activity of learning is carried out by carrying out activities of drawing conclusions and giving assignments. (3) Evaluation activities in the role playing method are carried out by assessing how students play the characters in the scenario. In addition, the teacher also gave a written test. (4) The advantages of the role playing method make it easier for students to understand the material, the weakness of the role playing method is that not all students have the ability to play characters according to the material (5) The application of the role playing method in social studies learning at MI Muhammadiyah Comparative has a positive impact on students and teachers . In addition, there are also negative impacts, including if students are not prepared properly there is a possibility that they will not do it seriously and are less than optimal, some children who do not participate in role playing become less active.